The Effect of Different Text Presentation Formats on Eye Movement Metrics in Reading - Selina Sharmin; Oleg Špakov; Kari-Jouko Räihä (Bern Open Publishing, 2012)
Eye movement data were collected and analyzed from 16 participants while they read text from a computer screen. Several text presentation formats were compared, including sentences as part of a full paragraph, sentences presented one by one, sentences presented in chunks of at most 30 characters at a predefined rate, and line-by-line presentation fitting the width of the computer screen. The goal of the experiment was to study how these different text presentation modes affect eye movement metrics (fixation duration, fixations per minute, regressions, etc.). One-way repeated measures ANOVA revealed that differences in presentation format have a significant effect on fixation duration, number of fixations per minute, and number of regressions.